하이퍼텍스트 특징을 활용한 글쓰기교육 - 이희영(Hee-Young Lee) (한국컴퓨터정보학회논문지, 2018)
This paper focuses on how the latest progress in digital media and technology affects the writing education environment. In the contemporary era, collecting numerous pices of information online, and arranging them to create new knowledge is important. There is also a need to seek new methods for writing education to stay in tune with the times. To that end, this paper suggests an open writing model using hypertexts. This writing model consists of a total of five stages, which are use of information, compilation of information, open mutual discussion, search of additional information and writing to recreate knowledge. The final outcome of such writing is writing using footnotes. By describing the gist of the keyword and adding numerous footnotes, such writing opens up an infinite possibility of re-creating information into new knowledge. This method can help university students who are accustomed to the digital society to proactively use information and improve multi-disciplinary communication skills required today. This author applied such a model to university writing education and found that more than 82% of the students were satisfied. Through the process of collaboration and recreation of knowledge in writing, learners found distinct benefits and noted their horizons had broadened. Given this effect, the open writing model using hypertexts is meaningful in that it forms a learning community that goes beyond a one-way feedback from instructor to student and instead nudges students to realize collective intellect. Moreover, it is meaningful in that it moves away from a top-down approach of the instructors passing down knowledge about writing and its rules, and towards a more proactive involvement by students in creating knowledge. KCI Citation Count: 1